Subversion of inflammasome activation and pyroptosis by pathogenic bacteria - Cunha, Larissa D.; Zamboni, Dario S. (Frontiers in Cellular and Infection Microbiology, 2013)
Activation of the inflammasome occurs in response to a notably high number of pathogenic microbes and is a broad innate immune response that effectively contributes to restriction of pathogen replication and generation of adaptive immunity. Activation of these platforms leads to caspase-1- and/or caspase-11-dependent secretion of proteins, including cytokines, and induction of a specific form of cell death called pyroptosis, which directly or indirectly contribute for restriction of pathogen replication. Not surprisingly, bona fide intracellular pathogens developed strategies for manipulation of cell death to guarantee intracellular replication. In this sense, the remarkable advances in the knowledge of the inflammasome field have been accompanied by several reports characterizing the inhibition of this platform by several pathogenic bacteria. Herein, we review some processes used by pathogenic bacteria, including Yersinia spp., Pseudomonas aeruginosa, Vibrio parahaemolyticus, Chlamydia trachomatis, Francisella tularensis, Shigella flexneri, Legionella pneumophila and Coxiella burnetii to evade the activation of the inflammasome and the induction of pyroptosis.